Prediction of Electromagnetic Wave Propagation in Troposphere Using Parabolic Equation and Two-Dimensional Refractivity - Choi, Seongro; Heo, Jun; Kim, Changseong; Wang, Sungsik; Choo, Hosung; Park, Yong Bae (Journal of Electrical Engineering and Technology, 2020)
In this paper, an analysis method of electromagnetic (EM) wave propagation in the troposphere is proposed using the parabolic equation (PE) and the actual two-dimensional modified refractivity (M-unit), that is, range and height dependent M-unit. Discrete Mixed Fourier Transform (DMFT) based PE method is used, and the validation is conducted using AREPS which is developed by the Space and Naval Warfare System Center of US NAVY. The M-units at the National Typhoon Center (NTC) in Jeju-island and meteorological station in Heuksan-island, South Korea are calculated using actual meteorological data. Then, two-dimensional M-unit is estimated using linear interpolation of M-unit at each position. The path loss between NTC and Heuksan-island is analyzed using the three types of M-unit data, Heuksan-island only, NTC only, and linear interpolation. The effect of two-dimensional M-unit on the EM wave propagation when considering long-range problem is discussed.
Keywords: Linear Interpolation; Meteorological data; Meteorological station; Mixed fourier transforms; Parabolic equation; Parabolic equation method; Parabolic Equations; Space and Naval warfare systems; Electromagnetic wave propagation; Parabolic equation method; Two-dimensional modified refractivity